PROBLEMATIKA YURIDIS PERLINDUNGAN HUKUM TENAGA MEDIS DAN TENAGA KESEHATAN PASCA PENGESAHAN UNDANG-UNDANG NOMOR 17 TAHUN 2023 - Ichsan Saputro; Shinta (Yayasan Merassa Indonesia Publikasi, 2026)
Legal protection for healthcare workers in Indonesia still faces serious challenges in the form of risks of criminalization, malpractice lawsuits, and violence in the workplace, despite the enactment of new regulations. This study aims to analyze the effectiveness of legal protection regulations for medical and healthcare workers following the enactment of Law Number 17 of 2023 concerning Health and to identify inhibiting factors and strengthening strategies. The research method used is normative juridical with a statutory approach and a conceptual approach. The results show that although the latest Health Law has attempted to synchronize norms through a professional protection mechanism, its implementation is still degraded by the ambiguity of the doctor-patient legal relationship and fragmented coordination between law enforcement institutions. The main inhibiting factors include low legal literacy among medical practitioners, minimal institutional advocacy in hospitals, and weak mechanisms for reporting violence. This study recommends the need for reconstruction of internal policies in healthcare facilities through the establishment of independent advocacy divisions and strengthening cross-sectoral synergy to ensure legal certainty and security for healthcare workers in carrying out their professional mandate.